2016
DOI: 10.1038/cddis.2016.243
|View full text |Cite
|
Sign up to set email alerts
|

Fucosylation of LAMP-1 and LAMP-2 by FUT1 correlates with lysosomal positioning and autophagic flux of breast cancer cells

Abstract: Alpha1,2-fucosyltransferases, FUT1 and FUT2, which transfer fucoses onto the terminal galactose of N-acetyl-lactosamine via α1,2-linkage have been shown to be highly expressed in various types of cancers. A few studies have shown the involvement of FUT1 substrates in tumor cell proliferation and migration. Lysosome-associated membrane protein 1, LAMP-1, has been reported to carry alpha1,2-fucosylated Lewis Y (LeY) antigens in breast cancer cells, however, the biological functions of LeY on LAMP-1 remain largel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 50 publications
1
30
0
1
Order By: Relevance
“…Autophagy is a highly dynamic process in mammalian cells. Therefore, monitoring autophagic flux is necessary for determining the rate of autophagy [32,33]. Autophagic flux was measured by comparing LC3II/β-actin levels in the cases of combination treatment with or without CQ (by increasing lysosomal pH) and long-lived protein p62 degradation.…”
Section: Combination Treatment Of Rp and ω-3 Pufas Blocks Autophagic mentioning
confidence: 99%
“…Autophagy is a highly dynamic process in mammalian cells. Therefore, monitoring autophagic flux is necessary for determining the rate of autophagy [32,33]. Autophagic flux was measured by comparing LC3II/β-actin levels in the cases of combination treatment with or without CQ (by increasing lysosomal pH) and long-lived protein p62 degradation.…”
Section: Combination Treatment Of Rp and ω-3 Pufas Blocks Autophagic mentioning
confidence: 99%
“…LAMP-1 is a multifunctional protein. It was reported previously that LAMP-1 was involved in apoptosis (31)(32)(33), autophagy (34,35), bacterial binding (36), and ARV p10 degradation (13). In this study, we show a new function of LAMP-1 in which LAMP-1 serves as a scaffold for both Siah-1 and p10 that allows the E3 ligase targeting p10 for ubiquitylation and degradation to suppress ARV infection.…”
Section: Discussionmentioning
confidence: 50%
“…In HeLa cells, HIV-1 counteracts metabolic and environmental stress-induced intracellular repositioning of lysosomes through enhancement of mTORC1 activity [51]. In another study, knockdown of FUT1 has been found to elevate the peripheral distribution of lysosomes by inhibition of mTORC1 activity, leading to the enhancement of autophagic flux [52]. All these previous findings demonstrate that the mTOR signaling pathway plays an important role in the regulation of lysosome positioning and trafficking.…”
Section: Autophagic Fluxmentioning
confidence: 89%